Potential modifiable factors associated with late-life cognitive trajectories - Wu, Zimu; Woods, Robyn L.; Chong, Trevor T. -J.; Orchard, Suzanne G.; McNeil, John J.; Shah, Raj C.; Wolfe, Rory; Murray, Anne M.; Storey, Elsdon; Ryan, Joanne (Frontiers in Neurology, 2022)
Objective: There is variability across individuals in cognitive aging. To investigate the direct/indirect associations of several modifiable factors with high cognitive performance, and cognitive decline. Methods: Data came from 17,724 community-dwelling individuals aged 65-98 years. Global cognition, verbal fluency, episodic memory, and psychomotor speed were assessed over up to seven years. Group-based multi-trajectory modeling identified distinct cognitive trajectories. Structural equation modeling examined the direct/indirect associations of social/behavioral factors and several chronic conditions with cognitive trajectories. Results: Seven subgroups with distinct trajectories across the four tests were identified. Participants with high cognitive performance (14.2%), and those with cognitive decline (4.1%), were compared to average cognitive performers (21.6%). Lower education, never alcohol intake, and frailty directly predicted increased risk of cognitive decline, and decreased likelihood of high cognitive performance. Hypertension (RR: 0.69, 95%CI: 0.60-0.80), obesity (RR: 0.84, 95%CI: 0.73-0.97), diabetes (RR: 0.69, 95%CI: 0.56-0.86) and depression (RR: 0.68, 95%CI: 0.54-0.85) only predicted lower likelihood of high cognitive performance, while dyslipidemia was only associated with cognitive decline (RR: 1.30, 95%CI: 1.07-1.57). Living alone predicted increased risk of cognitive decline and several comorbidities. Smoking did not predict cognitive trajectories but was associated with increased risk of diabetes, obesity and frailty. Conclusions: Although several modifiable factors were associated with high performance, and reversely with cognitive decline, this was not observed for obesity, hypertension and dyslipidemia. Further, health behaviors may affect cognitive function indirectly, via geriatric conditions. This indicates that strategies to promote healthy cognitive aging, may be distinct from those targeting dementia prevention.